2018
DOI: 10.1097/qai.0000000000001796
|View full text |Cite
|
Sign up to set email alerts
|

Trends Over Time for Adolescents Enrolling in HIV Care in Kenya, Tanzania, and Uganda From 2001–2014

Abstract: Expanding HIV services and ART coverage was likely associated with earlier adolescent enrollment and ART initiation but also with higher attrition rates before and after ART initiation. Interventions are needed to promote retention in care among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…Along with the two-fold increase in the proportion of younger adolescents and the three-fold increase in the proportion of older adolescents over the study period, their median CD4 count at ART start also increased from 2011–2013 and reached up to over 350 cells/μl in 2017–2020. This finding is consistent with that of Apondi et al who has shown similar increase in the proportion of older adolescents at ART start in their study in East Africa [ 29 ]. Implementation of the Treat All strategy, rise in HIV testing and linkage to care, education on the AIDS epidemic, and counselling are described by the authors as likely contributing factors to this increase [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Along with the two-fold increase in the proportion of younger adolescents and the three-fold increase in the proportion of older adolescents over the study period, their median CD4 count at ART start also increased from 2011–2013 and reached up to over 350 cells/μl in 2017–2020. This finding is consistent with that of Apondi et al who has shown similar increase in the proportion of older adolescents at ART start in their study in East Africa [ 29 ]. Implementation of the Treat All strategy, rise in HIV testing and linkage to care, education on the AIDS epidemic, and counselling are described by the authors as likely contributing factors to this increase [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with previous research that has highlighted a range of social and structural barriers to HIV The absolute effect of treatment eligibility expansions for young adolescents was greater under general Treat All policies than under earlier pediatric Treat All policies. This was noteworthy, given that large numbers of adult patients, newly-eligible under Treat All, could potentially strain HIV service provision, leading to the crowding out of vulnerable groups, such as young adolescents, for whom tailored interventions and services are recommended [11,15,[38][39][40]. These results lend support for the supposition that general Treat All policies, with harmonized treatment recommendations for different population groups, are easier to implement in real-world treatment settings than prior policies targeting specific groups.…”
Section: Discussionmentioning
confidence: 83%
“…Increases in rapid ART initiation were particularly large following national adoptions of a general Treat All policy (i.e., for all ages) in 2016 in Burundi, DRC, Kenya, Malawi, and Rwanda. Observed increases in the proportion of young adolescents rapidly initiating ART following national adoption of Treat All policies may have substantial clinical importance, given evidence indicating that young adolescents with perinatally-acquired HIV often enroll in care late and do not initiate ART until they are at advanced stages of disease [14,15,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors unique to this setting that were associated with attrition included male sex, residence outside Asmara, enrolment in later years and late presentation. In general, data on the relationship between sex and attrition are inconsistent, with most studies reporting a null relationship, while others skew toward either sex 8 26 27. We believe that these inconsistencies and paradoxical results in cohorts across SSA mirror the disparate context-specific influences in the region.…”
Section: Discussionmentioning
confidence: 90%